Critical Evaluation of Trends in Otolaryngology Resident Caseload by Subspecialty from 2005 to 2019. (August 2021) - Welschmeyer, Alexandra; Coerdt, Kathleen; Crossley, Jason; Malekzadeh, Sonya
Background: Subspecialty caseloads logged by otolaryngology residents over the last 15 years is currently unknown. This study examines the trends at the national level. Methods: Otolaryngology case log data was collected from the Accreditation Council for Graduate Medical Education (ACGME) from 2005 to 2019. Data were categorized according to the following surgical subspecialties: pediatrics, rhinology/skull base, head and neck, facial plastics, otology, and laryngology. Linear regression analyses were performed for each procedure within each subspecialty, total subspecialty means, and total caseload means across all years. Results: Overall surgical volume significantly increased between 2005 and 2019 ( P < .0001); however, there was a significant decline in pediatrics procedures ( R 2 = 0.80, P < .0001). Rhinology/skull base procedures increased the most drastically ( R 2 = 0.96, P < .0001). Conclusion: While total mean resident case logs have steadily increased between 2005 and 2019, pediatric cases have declined substantially due to fewer tympanostomy tube insertions and adenotonsillectomies. Rhinology/skull base procedures have increased most significantly secondary to an increase in endoscopic sinus surgeries. Despite changes in case volume amongst specialties, the annual increase in resident case load suggests that otolaryngology residents are meeting the demands of their graduate medical training.